Proyek “Melukis di Atas Talenan” Terintegrasi STEAM-Tri N Untuk Mengembangkan Kreativitas Siswa - Lestariningsih, Dwi; Bariyah, Insanul Qisti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
One of the skills required for 21st century skills is creative thinking skills. Creative thinking is inseparable from the term creativity. Low student creativity is caused by the use of methods, models, and learning strategies that do not support students' creativity. The purpose of this study was to describe the real conditions of the STEAM-Tri N Integrated "Painting on a Cutting Board" project to develop student creativity. This study used descriptive qualitative research. The subjects of this study were 1st grade students with 17 male students and 10 female students. Data collection techniques used were observation, interviews, and documentation. The results of the study were that the STEAM-Tri N integrated "Painting on a Cutting Board" project was able to develop the creativity of elementary school students. The development of student creativity is accompanied by the quality of innovative, creative, and enjoyable learning because there is a significant correlation between the learning model and the development of creativity. Project-based learning "Painting on a Cutting Board" is integrated learning for three learning loads, namely Mathematics, Arts and Culture, and P5 (Pancasila Student Profile Strengthening Project).